2022
DOI: 10.31234/osf.io/3e4zb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

powe(R)OC: A power simulation tool for eyewitness lineup ROC analyses

Abstract: Receiver operating characteristic (ROC) curve analyses have become increasingly common in eyewitness lineup experiments, yet statistical power for these analyses is not well-understood. powe(R)OC is a free, open-source R Shiny web app that allows users with minimal programming and statistical knowledge to conduct simulation-based power analyses for two-condition (e.g., simultaneous vs. sequential lineups) eyewitness lineup experiments (and certain other recognition memory experiments) that use ROC analysis. po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…These findings highlight the need for researchers to conduct power analyses and make them reproducible just as their data and analyses (Lakens, 2022;Hardwicke et al, 2022). Although power analyses for ROC curve analyses and AUC values can be conducted via the R package "pROC" (Robin et al, 2011), further work is necessary to allow more contextualized power analyses using for example the SESOI (but see Mah, 2022).…”
Section: Smallest Effect Size Of Interest In Eyewitness Memory Researchmentioning
confidence: 99%
“…These findings highlight the need for researchers to conduct power analyses and make them reproducible just as their data and analyses (Lakens, 2022;Hardwicke et al, 2022). Although power analyses for ROC curve analyses and AUC values can be conducted via the R package "pROC" (Robin et al, 2011), further work is necessary to allow more contextualized power analyses using for example the SESOI (but see Mah, 2022).…”
Section: Smallest Effect Size Of Interest In Eyewitness Memory Researchmentioning
confidence: 99%
“…A power analysis was conducted using the powe(R)OC app in R (Mah, 2022). This analysis indicated that 400 participants are required in order to detect an effect size of 0.15 with approximately 0.8 power.…”
Section: Participantsmentioning
confidence: 99%
“…There is some overlapping functionality between sdtlu and pyWitness, but the main differences are the available models that each package supports, the possibility of extension, and us-ability. Recently an R shiny app, powe(R)OC, has been made available to perform power analyses for eyewitness ROCs (Mah (2022)). These technological solutions will advance the way researchers conduct eyewitness ID analyses.…”
Section: Introductionmentioning
confidence: 99%